Ceftazidime as an empiric therapy for neonatal sepsis - Indrayady Indrayady; Afifa Ramadanti; Yulia Iriani; Herka Pratama Putra (Indonesian Pediatric Society, 2021)
Background Sepsis is still the leading cause of death in neonates in developing countries. Proper administration of antibiotics is important for managing neonatal sepsis. The microorganisms that cause neonatal sepsis, as well as their sensitivity patterns, change over time and differ from one place to another. Since 2001, ceftazidime has been used as an empirical antibiotic for managing neonatal sepsis at Dr. Mohammad Hoesin Hospital, Palembang, South Sumatera, but its effectiveness is questionable. Objective To evaluate the effectiveness of ceftazidime as an empiric therapy for neonatal sepsis. Methods This study was pre-experimental, for one group, pre- and post-test, was conducted in 49 neonates with neonatal sepsis in the Neonatal Ward at Dr. Mohammad Hoesin Hospital, Palembang, South Sumatera, from April to September 2019. The effectiveness of ceftazidime was determined based on clinical and laboratory improvements 72 hours after ceftazidime administration. Results Of 49 neonates, 28 experienced clinical and laboratory improvement, while 21 experienced improvement in only one parameter, either clinical or laboratory. Gram positive bacteria were found in 22/49 subjects. Conclusion There is a significant difference on white blood cell count and CRP level between before and after ceftazidime administration but overall ceftazidime is no longer effective as empiric antibiotic therapy in neonatal sepsis.